2020
DOI: 10.1177/1071100720942140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Complication Rates and Outcomes Following First Metatarsophalangeal Arthrodesis for Hallux Rigidus

Abstract: Background: Hallux rigidus is one of the most common toe pathologies in patients greater than 50 years old. Although metatarsophalangeal (MTP) arthrodesis is used to improve pain and function, older patients are often considered to be higher-risk operative candidates. There are minimal data on outcomes of MTP fusion and no studies comparing outcomes between geriatric and younger patients. Methods: This is a single-center, prospective study of all patients who underwent MTP fusion between August 1, 2015, and Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…In a quite similar study with a much shorter follow-up (1 year postoperatively), no difference in pain and function was found between young and old patients. 23 The main difference for this discrepancy with our study we see in the age cutoff, with young patients defined as age ≤65 years, for us up to 50 years, but also the follow-up time and the other clinical scores might have had an influence (ie, 36-Item Short Form Health Survey [SF-36] and Life-Space Assessment survey [LSA]). Another study showed that in young patients (mean age 49 years), 96% (n = 48/50) were satisfied with their level of sports activity after 1-2 years following MTP I arthrodesis.…”
Section: Discussioncontrasting
confidence: 56%
“…In a quite similar study with a much shorter follow-up (1 year postoperatively), no difference in pain and function was found between young and old patients. 23 The main difference for this discrepancy with our study we see in the age cutoff, with young patients defined as age ≤65 years, for us up to 50 years, but also the follow-up time and the other clinical scores might have had an influence (ie, 36-Item Short Form Health Survey [SF-36] and Life-Space Assessment survey [LSA]). Another study showed that in young patients (mean age 49 years), 96% (n = 48/50) were satisfied with their level of sports activity after 1-2 years following MTP I arthrodesis.…”
Section: Discussioncontrasting
confidence: 56%
“…In the same vein, Vermersch et al 39 found that older patients did not have an increased rate of delayed healing, deep infections, and nonunion after forefoot surgery. Lunati et al 20 also reported that patients aged ≥65 years old and those younger than 65 years had similar rates of postoperative wound complications, deep vein thrombosis, or reoperations for complications after metatarsophalangeal arthrodesis for hallux rigidus, although the older group had a greater number of comorbidities. Overall, these findings suggest that increasing age had little influence on the perioperative outcomes of hallux valgus surgery, likely owing to the low surgical morbidity of the procedure.…”
Section: Discussionmentioning
confidence: 97%
“…Positive results in the surgical fixation of both hallux rigidus and hallux valgus are well documented across age groups. 7,19 Metatarsophalangeal (MTP) fusion is a reliable method for the treatment of hallux rigidus and is associated with high patient satisfaction and improved functionality. 7 Nevertheless, the effects of psychiatric disorders on surgical outcomes in this population are not well understood.…”
Section: Introductionmentioning
confidence: 99%